A comprehensive overview of fixed-volume hemorrhage effects in New Zealand White rabbit models - Dwi Utari Rahmiati; Gunanti Gunanti; Deni Noviana; Raden Harry Soehartono; Eva Harlina (Open Veterinary Journal)
Background: Hemorrhagic shock is a life-threatening condition resulting from acute blood loss, leading to compromised tissue perfusion and organ dysfunction. Currently, the guidelines for categorizing and managing hemorrhagic shock in pets are based on protocols developed for humans.